Penelitian Pembuatan Formulasi Insektisida Dari Tanaman Nimba - Sri Pudji Rahayu; Rofienda Rofienda; Emmy Ratnawati (Jurnal Kimia dan Kemasan, 1996)
Neem tree (Azadirachta indica) was found contain azadirachtion that can be used as an insecticide. Extraction of azadirachtin has been conducted in BEIK laboratory with neem seed collected from Madura and Ngawi, by using n-hexane, methanol petroleum ether and ethyl acetate as solvents. The experiment showed that n-hexane gave the best result in the extraction of neem seed from Madura, that was 20,36 °10. The neem extract then used to made Emulsifiable Concentrate (EC) formulation of insecticide. As a control, it was used neem oil from India.From the physico - chemical testing of formulation, is found that EC formulation of neem extract arc not give good result yet, compared then EC formulation that made from Indian neem oil.